Renegotiating power in adult safeguarding: the role of advocacy. Issue 2 (10th April 2017) - Lonbay, Sarah P.; Brandon, Toby
Abstract : Purpose: The increased involvement of adults at risk in the safeguarding process has become a prominent issue within English safeguarding policy. However, there is evidence to suggest that actual levels of involvement are still low. The purpose of this paper is to present findings from a PhD study in relation to the benefits of advocacy in supporting this involvement in adult safeguarding for older people. Design/methodology/approach: Participants in the study included advocates and social workers who had experience of working with older people through the safeguarding process within two North East England local authorities. A critical realist approach through in-depth interviews was taken with all the participants. Findings: The research findings in relation to the benefits of advocacy in supporting older people going through safeguarding processes are reported. The practical limitations and factors which help and hinder advocacy support within the process are also considered. The theoretical implications for power, empowerment, and advocacy are also explored. Research limitations/implications: A key limitation of this research is that it did not include older people who had been through safeguarding amongst the participants. Practical implications: Key implications for practice and policy are discussed. Originality/value: The paper provides an overview and critique of empowerment in adult safeguarding and the role that advocates play in promoting this key principle.